The evaluation of endothelial function and structure in hirsute patients in reproductive age - YOLDEMİR, AHMET TEVFİK; YAVUZ, DİLEK (ELSEVIER SCIENCE BV, 2016)
Objective: To evaluate the endothelial function and structure in patients with hirsutism in reproductive age. Study design: The study was conducted on 69 consecutive women admitted with complaints of hirsutism and 63 voluntary healthy women, as controls. A total of 132 subjects who applied to the Gynecology and Infertility Outpatient Clinics were included. Participants with modified Ferriman Gallway (mFG) score over 8 were considered to be hirsute. The demographic, metabolic, hormonal characteristics, risk factors of cardiovascular disease, CIMT (carotis intima media thickness) and FMD (flow-mediated dilatation) were compared between hirsute women and those in the control group. A prospective case-control study was performed. Results: There was no statistically significant difference in CIMT (0,50 0,08 vs 0,52 0,08, p = 038) and FMD (10,80 6,83 vs 9,57 6,52, p = 0.34) values between the study and control groups, respectively. There was no statistically significant correleation between CIMT and FMD values with age, body mass index (BMI), waist circumference, hip circumference, waist/hip ratio, CRP (C-reactive protein), total cholesterol, LDL (low density lipoprotein), HDL (high density lipoprotein), total testosteron, FAI (free androjen index), androstenedion, SHBG (sex hormone binding globuline), DHEA-S, hirsutism score, sistolic blood pressure, diastolic blood pressure, HOMA-IR (homeostatic model of assesment insuline resistance) value. Conclusion: The effect of the presence of hirsutism on either CIMT and FMD values, among young patients was not significant. Since endothelial dysfunction might became evident after a long period of physiopathological process, our findings obtained from younger patients may not really show the impact of hirsutism on endothelial function in short term. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Hirsutism; Endothelial dysfunction; Flow mediated dilatation; Carotis intima media thickness; FMD; CIMT; POLYCYSTIC-OVARY-SYNDROME; PREMATURE CAROTID ATHEROSCLEROSIS; CORONARY-HEART-DISEASE; YOUNG-WOMEN; CARDIOVASCULAR RISK; DENSITY-LIPOPROTEIN; INSULIN-RESISTANCE; ANDROGEN EXCESS; MEDIA THICKNESS; DYSFUNCTION